2021
DOI: 10.1002/humu.24294
|View full text |Cite
|
Sign up to set email alerts
|

Targeted massively parallel sequencing of candidate regions on chromosome 22q predisposing to multiple schwannomas: An analysis of 51 individuals in a single‐center experience

Abstract: Constitutional LZTR1 or SMARCB1 pathogenic variants (PVs) have been found in ∼86% of familial and ∼40% of sporadic schwannomatosis cases. Hence, we performed massively parallel sequencing of the entire LZTR1, SMARCB1, and NF2 genomic loci in 35 individuals with schwannomas negative for constitutional first‐hit PVs in the LZTR1/SMARCB1/NF2 coding sequences; however, with 22q deletion and/or a different NF2 PV in each tumor, including six cases with only one tumor available. Furthermore, we verified whether any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Some SMARCB1/LZTR1 PVs, missed by current diagnostic methods, may reside in untranslated regions or nearby regions that may affect expression (position effect). 21,38 However, additional genes are likely to be discovered. For instance, a 3-generation family and an unrelated sporadic case with multiple schwannomas and multinodular goiter have now been described with the same DGCR8 PV (c.1552G>A; p.E518K) on chromosome 22q that showed the same 3 event/4 hit mechanism as SMARCB1/LZTR1 in 9 schwannomas, with 4 additional schwannomas showing somatic loss of the entire chromosome 22.…”
Section: Identifying Additional Genes That Cause Swnmentioning
confidence: 99%
“…Some SMARCB1/LZTR1 PVs, missed by current diagnostic methods, may reside in untranslated regions or nearby regions that may affect expression (position effect). 21,38 However, additional genes are likely to be discovered. For instance, a 3-generation family and an unrelated sporadic case with multiple schwannomas and multinodular goiter have now been described with the same DGCR8 PV (c.1552G>A; p.E518K) on chromosome 22q that showed the same 3 event/4 hit mechanism as SMARCB1/LZTR1 in 9 schwannomas, with 4 additional schwannomas showing somatic loss of the entire chromosome 22.…”
Section: Identifying Additional Genes That Cause Swnmentioning
confidence: 99%
“…Indeed a deep intronic PV, NM_003073.5:c.795+1498C>T, leading to the inclusion of a cryptic exon and a truncated product, has previously been reported in intron 6 of SMARCB1 (Smith et al, 2020). In addition, a recent deep massive parallel sequencing study of 35 schwannomatosis cases (Piotrowski et al, 2021) reported two novel deep intronic variants in intron 4 of SMARCB1 (NM_003073.5:c.500+883T>G and NM_003073.5:c.500+887G>A). Both of these variants were further characterized by means of RNA analysis and demonstrated to result in retention of part of intron 4 and a truncated transcript.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of copy number variants is also routinely assessed Primers were designed to target flanking sites at each side of exons for regions of COQ6 (NM_182476.2), DGCR8 (NM_022720.6), CDKN2A (NM_000077.4), and CDKN2B (NM_004936.3) and are listed in Supporting Information: Table S3. In addition, two intronic regions of SMARCB1 known to harbor PVs for schwannomatosis (Piotrowski et al, 2021;Smith et al, 2020) were also screened.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has found that SGSM1 degradation led to the invasion and metastasis of nasopharyngeal carcinoma [ 14 ]. Another parallel sequencing research has shown that SGSM1 was a potential candidate gene for schwannomatosis [ 15 ]. However, the role of SGSM1 has hardly been studied and its prognostic value in LGGs remained unclear.…”
Section: Introductionmentioning
confidence: 99%